Low Cycle Fatigue behavior of AA7075 with surface gradient structure produced by Ultrasonic Shot Peening - Pandey V.; Chattopadhyay K.; Santhi Srinivas N.C.; Singh V. (My University, 2025)
Effect of ultrasonic shot peening (USSP) for different durations, with graded surface structures, was studied on low cycle fatigue behavior of the aluminium alloy 7075 (AA7075) at room temperature. LCF tests were conducted at different total strain amplitudes. Surface microstructures of the USSP treated specimens were characterized using X-ray diffraction and transmission-electron microscopy. No phase change was found due to USSP. Surface region of the ultrasonically shot peened sample was found to develop nanosize grains of 16-20 nm. Significant improvement was observed in LCF life of the specimen subjected to USSP for 180 seconds. However, LCF life of the sample USSPed for long duration of 300 seconds was reduced. The higher fatigue life resulting from USSP for 180 seconds, may be attributed to increased resistance of the USSPed sample against fatigue crack initiation, due to grain refinement in the surface region. © 2016 The Authors. Published by Elsevier B.V.